Fully transparent high performance thin film transistors with bilayer ITO/Al-Sn-Zn-O channel structures fabricated on glass substrate - Yingying Cong (Nature Portfolio, 2017)
Abstract In this work, fully transparent high performance double-channel indium-tin-oxide/Al–Sn–Zn–O thin-film transistors (ITO/ATZO TFTs) are successfully fabricated on glass by radio frequency (RF) magnetron sputtering. The ITO layer acts as the bottom channel layer to increase the channel carrier concentration. The top ATZO channel layer, which is deposited via high oxygen partial pressure in the sputtering process, is useful to control the minimum off-state current. After annealing, the ITO/ATZO TFT demonstrates outstanding electrical performances, including a high ON/OFF current ratio (Ion/Ioff) of 3.5 × 108, a steep threshold swing (SS) of 142.2 mV/decade, a superior saturation mobility (μsat) of 246.0 cm2/Vs, and a threshold voltage VT of 0.5 V. The operation mechanisms for double-channel structures are also clarified.